Critical current improvement and resistance evaluation of superconducting joint between Bi2223 tapes. (12th January 2022) - Takeda, Y; Kobayashi, K; Uchida, A; Kitaguchi, H; Nishijima, G; Yanagisawa, Y; Nakashima, T; Yamade, S; Kobayashi, S; Kato, T; Nakamura, S; Motoki, T; et al.
Abstract: We improved the critical current ( I c ) of the superconducting joint between the Bi2223 tapes by introducing the two-step sintering process. The in-field transport I c of ∼300 A at 4.2 K and 1 T under a 10 −9 Ω criterion was successfully demonstrated. The I c improvement can probably be attributed to the enhancement of the intergrain critical current density for a Bi2223 intermediate layer. Ultra-low in-field joint resistance below 10 −14 Ω at 4.2 K and 1 T was also demonstrated using current decay measurement. To the best of our knowledge, this study is the first to demonstrate a practical level of in-field transport I c and ultra-low in-field joint resistance for the superconducting joint between Bi2223 tapes. We believe that this superconducting joint technology will facilitate development of persistent current mode Bi2223 superconducting magnets.